Pemanfaatan Artificial Intelligence (AI) Dalam Meningkatkan Efektivitas Pembelajaran PAI - karmilah; Patimah, Siti; Bachtiar, Machdum; Tihami, M.A; Ahmad Lughowi, Rifyal (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
The Society 5.0 era demands the use of technology, including Artificial Intelligence (AI), to increase the effectiveness of learning, especially Islamic Religious Education (PAI). This study aims to analyze the use of Artificial Intelligence in PAI learning at SMAN 18 Tangerang Regency, focusing on its benefits, challenges, and impact on teacher-student interaction. The research method uses a qualitative approach with a case study design, involving semi-structured interviews and observations of teachers and students. The results of the study show that Artificial Intelligence provides significant benefits, such as personalized learning, increased interactivity, and administrative efficiency. However, challenges such as teacher-student readiness, content suitability with Islamic values, and the risk of technology dependence need to be addressed. In conclusion, Artificial Intelligence has the potential to improve the quality of PAI learning if used wisely and in accordance with Islamic principles. This study recommends careful integration of Artificial Intelligence, paying attention to ethical aspects and Islamic values.